(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Systemic administration of clindamycin-hydrochloride (an antibiotic) is mainly associated with gastro-intestinal disturbances and allergic reactions. Little is known of its haematological and biochemical toxicity. Objective: To evaluate the haematological and biochemical changes associated with indiscriminate administration of oral clindamycin-hydrochloride in clinically healthy rodents. Materials and Methods: Twenty Wistar rats (130-189 grams) divided into four groups (A-D) of five rats each were used. Rats in group A (control) were treated with distilled water. Groups B-D received 0.2mL (below normal dose), 0.4mL (normal dose) and 1.0mL (above normal dose) of clindamycin-hydrochloride (75mg/5mL) at 8 hourly intervals, three times daily for 14 days, respectively. Thereafter, blood was collected through both ocular and cardiac puncture into ethylene diamine tetra acetic acid (EDTA) and lithium heparin bottles for evaluation of haematological and biochemical parameters, respectively. Results: Significant (P < 0.05) increases in total white blood cell (WBC) counts and decreases in eosinophil (Eos) counts occurred in clindamycin-treated rats. In addition, significant (P < 0.05) increases in concentrations of Total cholesterol, Triglyceride and High-density lipoprotein, respectively, as well as decreases in concentrations of Albumin, Alanine transaminase and Gamma-glutamyl transpeptidase, respectively also occurred in clindamycin-treated rats. Conclusion: Indiscriminate use of clindamycin-hydrochloride produces adverse haematological and biochemical changes in Wistar rats which may be a reflection of systemic toxicity, allergic reaction as well as liver and kidney dysfunction.